Penggunaan aplikasi augmented reality untuk memfasilitasi penguasaan konsep peserta didik tentang siklus hidup tumbuhan dan keterampilan berpikir kreatif - Mardiyah, Fitri Husni; Widodo, Ari; Rochintaniawati, Diana (Department of Biology Education, Universitas Pendidikan Indonesia, 2020)
Augmented reality application-based learning is one form of education reforms that is used to improve various skills that are needed. One of them is creative thinking skills to face the challenges of the 21st century or the challenges of the industrial revolution 4.0 today. Therefore, the researcher conducts a study entitled the use of augmented reality application to improve the understanding of plant life cycle and creative thinking skills. This study aims to analyze the effects of the use of augmented reality application based on the improved understanding of students about the plant life cycle and creative thinking skills. This study uses the method of quasi-experimental design. The used study design is non-eqivalent control group pretest-postest design. The samples in this study are grade X students of SMA 2 Lembang consisting of 30 students determined by purposive sampling technique. The results of this study show that there are significant differences in the understanding of the concept and creative thinking skills of the students, although the creative thinking skills in both classes are still in the poor category., it is due to the application media of augmented reality application is only used as a medium of learning without including the making process of it so students are not accustomed when they are faced with questions in the form of problem. The test of two averages on the value of concept understanding shows the figure of (2-tailed t = 0 and 0,001) Î± (0.05) which means that augmented reality application-based learning has an influence on students 'mastery of concept concepts, but does not affect the ability of participants' creative thinking skills students.